2019
DOI: 10.1101/2019.12.16.869131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ectopic overexpression of abiotic stress-induced rice annexin,OsAnn5potentiates tolerance to abiotic stresses

Abstract: The current study on putative rice annexin OsAnn5 was tried to know its functional role in the abiotic stress tolerance. For this an in silico analysis of its protein sequence and upstream region was carried out. This results in identification of several probable potential sites for posttranslational modifications and cis-elements respectively. We have studied the effect of OsAnn5 in the amelioration of abiotic stress tolerance through heterologous expression in transgenic tobacco and E.coli. It is observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
1
0
0
Order By: Relevance
“…The results suggested that CaAnn9-mediated oxidative stress tolerance, caused by salt stress, was through the regulation of antioxidant enzymes. This correlation has also been observed with other Ann transgenes [17,39]. For example, under stress conditions, the overexpression of OsAnn5 enhanced the tolerance to abiotic stress by effectively eliminating ROS and balancing the expression of SOD and CAT antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 63%
“…The results suggested that CaAnn9-mediated oxidative stress tolerance, caused by salt stress, was through the regulation of antioxidant enzymes. This correlation has also been observed with other Ann transgenes [17,39]. For example, under stress conditions, the overexpression of OsAnn5 enhanced the tolerance to abiotic stress by effectively eliminating ROS and balancing the expression of SOD and CAT antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 63%